Conductive Education as a Method of Stroke Rehabilitation: A Single Blinded Randomised Controlled Feasibility Study. (23rd June 2016) - Bek, Judith; Brown, Melanie R.; Jutley-Neilson, Jagjeet; Russell, Nicholas C. C.; Huber, Pia A. J.; Sackley, Catherine M.
Abstract : Background. Conductive Education for stroke survivors has shown promise but randomised evidence is unavailable. This study assessed the feasibility of a definitive randomised controlled trial to evaluate efficacy. Methods. Adult stroke survivors were recruited through local community notices. Those completing the baseline assessment were randomised using an online program and group allocation was independent. Intervention group participants received 10 weekly 1.5-hour sessions of Conductive Education at the National Institute of Conductive Education in Birmingham, UK. The control group participants attended two group meetings. The study evaluated the feasibility of recruitment procedures, delivery of the intervention, retention of participants, and appropriateness of outcome measures and data collection methods. Independent assessments included the Barthel Index, the Stroke Impact Scale, the Timed Up and Go test, and the Hospital Anxiety and Depression Scale. Results. Eighty-two patients were enrolled; 77 completed the baseline assessment (46 men, mean age 62.1 yrs.) and were randomised. 70 commenced the intervention (n = 37 ) or an equivalent waiting period (n = 33 ). 32/37 completed the 10-week training and 32/33 the waiting period. There were no missing items from completed questionnaires and no adverse events. Discussion. Recruitment, intervention, and assessment methods worked well. Transport issues for intervention and assessment appointments require review. Conclusion. A definitive trial is feasible. This trial is registered with ISRCTN84064492 .